Transactivation of TrkB Receptors by Oxytocin and Its G Protein-Coupled Receptor - Mitre, Mariela; Saadipour, Khalil; Williams, Kevin; Khatri, Latika; Froemke, Robert C.; Chao, Moses V. (Frontiers in Molecular Neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF) binds to the TrkB tyrosine kinase receptor, which dictates the sensitivity of neurons to BDNF. A unique feature of TrkB is the ability to be activated by small molecules in a process called transactivation. Here we report that the brain neuropeptide oxytocin increases BDNF TrkB activity in primary cortical neurons and in the mammalian neocortex during postnatal development. Oxytocin produces its effects through a G protein-coupled receptor (GPCR), however, the receptor signaling events that account for its actions have not fully defined. We find oxytocin rapidly transactivates TrkB receptors in bath application of acute brain slices of 2-week-old mice and in primary cortical culture by increasing TrkB receptor tyrosine phosphorylation. Because oxytocin displays pro-social functions on maternal care, cognition and social attachment, it is currently a focus of therapeutic strategies in autism spectrum disorders. Interestingly, oxytocin and BDNF are both implicated in the pathophysiology of depression, schizophrenia, anxiety and cognition. The transactivation of TrkB receptors by oxytocin enhances the clustering of gephyrin, a scaffold protein responsible for coordinating inhibitory responses. These results imply that oxytocin may rely upon crosstalk with BDNF signaling to facilitate its actions through receptor transactivation.